Pengaruh Implementasi Kebijakan Reformasi Birokrasi Terhadap Efektivitas Organisasi Di Sekretariat Daerah Kabupaten Bolaang Mongondow Utara - Ginting, Yeni Paramitha; Rompas, Wilson Yappy (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract:. This study is how bureaucracy reform policy implementation at the Regional Secretariat Bolaang North Mongindow, and whether there is influence of the bureaucratic reform policy implementation on organizational effectiveness. The method used in this study is a quantitative method. Sources of data / research respondents were as many as 37 employees were taken by random sampling technique from 73 employees of the Secretariat Regional North Bolaang Bolaang. Collecting data using questionnaires and assisted with interviewing techniques. The analysis technique used is the percentage analysis, linear regression analysis and product moment correlation.Results of data analysis showed: (1) variable regression coefficient bureaucratic reform policy implementation to increase organizational effectiveness is significant posifive and (2) the correlation coefficient and the coefficient of determination bureaucratic reform policy implementation variables on organizational effectiveness is significant. Based on the results of that study concluded: (1) Implementation of bureaucratic reform policies in the Regional Secretariat Bolaang North Bolaang basically met the criteria efficient, effective, and rational as mandated by Government Regulation No. 41 of 2007. (2) The effectiveness of the organization in the Regional Secretariat Bolaang North Bolaang generally high enough / good, (3) the implementation of bureaucratic reform policies have a relationship and a positive and significant impact on the effectiveness of the organization in the Regional Secretariat Bolaang Bolaang. Keywords: reform of the bureaucracy, organizational effectiveness